Economic impact of avian infectious laryngotracheitis in a broilers farm in Lima, Perú - López L., Lupe (2015)
The aim of this study was to quantify the economic impact of avian infectious laryngotracheitis (ILT) on productive and economic performance of broilers. Two batches of 35 000 broilers each up to 49 days of age were evaluated. The first batch was affected for ILT while the other was not affected. A survey was conducted to collect information about productive data, biosecurity and production cost per batch, as well as additional costs related to the control of the disease. The economic impact was evaluated by comparing data from both batches using a stochastic distribution model with the risk analysis program @Risk 5.1®. Besides, a statistical analysis was done to determine difference between productive data of the two batches. In the one with ILT the mortality increased by 3.51% and feed conversion rate by 16.8%, while the productive efficiency decreased by 27.3% compared with the batch without ILT. The total economical loses due the disease were S/. 88,805. The risk analysis showed a range of losses from S/. 28,800.00 to S/. 149,300.00 for the 35 000 broilers with ILT.